Maternal plasma cell-free DNA nucleosome footprints can reveal changes in gene expression profiles during pregnancy and pre-eclampsia - Kun Li; Zhiwei Guo; Fenxia Li; Shijing Lu; Min Zhang; Xingyu Wei; Chao Sheng; Wenbo Hao; Xuexi Yang (BMC Pregnancy and Childbirth)
Abstract Background Differential gene expression analysis is important to understand pregnancy processes and disease development. However, no non-invasive and comprehensive methods exist to identify differentially expressed genes (DEGs) in the fetus and placenta during pregnancy or pregnancy complications. Nucleosome footprints in maternal peripheral blood plasma cell-free DNA (cfDNA) reflect the gene expression profile of the cell of origin, mainly immune cells in the maternal blood and placenta. This study aimed to validate the feasibility of detecting changes in gene expression profiles as differentially depth gene (DDGs) based on plasma nucleosome footprints as a potential biomarker for pregnancy and pre-eclampsia. Methods Deep sequencing was performed on separated plasma cfDNA collected from 34 women, including eight non-pregnant women, 14 healthy pregnant women, and 12 pre-eclamptic pregnant women. The number of reads in the promoter region of each gene was extracted and normalized. Normalized depths of genes were compared between healthy pregnant vs. non-pregnant women, all pregnant women vs. non-pregnant women, and healthy pregnant women vs. pre-eclamptic pregnant women using the Wilcoxon rank-sum test to identify statistically significant DDGs. The roles of these genes were identified by functional enrichment analysis using gene ontology. Results Plasma cfDNA revealed different nucleosome footprints in preeclampsia pregnant, healthy pregnant, and non-pregnant women. Gene annotation revealed that the functions of 629 DDGs in pregnant and non-pregnant women mainly involved immune regulation, regardless of pre-eclampsia. 1978 DDGs between healthy pregnant and pre-eclamptic pregnant women displayed differences in immune regulation, cell cycle regulation, and sensory perception. These results are consistent with prior microarray and RNA-sequencing data. Conclusions The depth of the cfDNA nucleosome footprint in maternal plasma can be used to reflect changes in the gene expression profile during pregnancy and pre-eclampsia. The plasma cfDNA nucleosome footprint is a potential non-invasive biomarker for pregnancy and placental-origin pregnancy complications.